2018
DOI: 10.1371/journal.pone.0203312
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and assessment of HBV chronically infected patients: Identification of those eligible for treatment in the South West region of Cameroon

Abstract: BackgroundThe management of patients with chronic hepatitis B infection is quite complex because it requires an in-depth knowledge of the natural history of the disease. This study was aimed at characterizing HBV infected patients in order to determine the phase of the infection and identify the proportion eligible for treatment using 3 different guidelines.MethodsHBV chronically infected patients (negative for HIV and HCV) were enrolled and the following tests were done for them: ALT, AST, HBV viral load, HBV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 34 publications
6
17
0
Order By: Relevance
“…This study documented a higher proportion HBeAg negative (93.2%) compared to HBeAg positive (6.8%) patients in congruence with studies such as conducted by Di Bisceglie, et al [26]. Four out of ive our patients were in a low replicative phase of chronic hepatitis B characterized by HBeAg-negative status, detection of HBe antibodies (anti-HBe), and DNA concentration below 2000 IU/mL with normal ALT, who are considered as chronic inactive carriers in similar proportion to what some studies have shown [27][28][29][30]. The determination of high percentage of HBeAg negative patients with low HBV viral loads in our study implies that most of the HBV patients are not eligible for antiviral therapy due to minimal or absent liver injury with low risk of disease progression [12].…”
Section: Discussionsupporting
confidence: 88%
“…This study documented a higher proportion HBeAg negative (93.2%) compared to HBeAg positive (6.8%) patients in congruence with studies such as conducted by Di Bisceglie, et al [26]. Four out of ive our patients were in a low replicative phase of chronic hepatitis B characterized by HBeAg-negative status, detection of HBe antibodies (anti-HBe), and DNA concentration below 2000 IU/mL with normal ALT, who are considered as chronic inactive carriers in similar proportion to what some studies have shown [27][28][29][30]. The determination of high percentage of HBeAg negative patients with low HBV viral loads in our study implies that most of the HBV patients are not eligible for antiviral therapy due to minimal or absent liver injury with low risk of disease progression [12].…”
Section: Discussionsupporting
confidence: 88%
“…Our study showed that males were more associated with HBV infection as compared to females. This has been established in previous studies [12,14,15] and could be attributed to hormonal and some protein expression differences. Oestrogen has been shown to play a protective role in females at reproductive age [16][17][18].…”
Section: Discussionsupporting
confidence: 70%
“…The HBV infected participants were earlier identified and enrolled as described in a previous study. 19 They subsequently linked us to their SPs and HHCs.…”
Section: Methodsmentioning
confidence: 99%
“…Chronic HBV patients enrolled in a previous study 19 at the Buea Regional Hospital between January 2016 and December 2017 linked us to their SPs and HHCs who were subsequently enrolled in this study. The high prevalence (8.0%) of HBV infection in the Southwest region of Cameroon 22 requires that we consider any HHC and/or SP of an HBV infected patient at risk of contracting the infection.…”
Section: Methodsmentioning
confidence: 99%